Inhibition of tyrosine phosphatases antagonizes CD95‐mediated apoptosis - Hehner, Steffen Peter; Hofmann, Thomas G.; Dröge, Wulf (EJB, 2001)
Ligation of the CD95 receptor resulted in a transient increase of cellular tyrosine phosphorylation. The inhibition of protein tyrosine phosphatases by pervanadate, a potent activator of B cells and T cells through the induction of tyrosine phosphorylation and downstream signaling events in the activation cascade, antagonized CD95‐triggered apoptosis.
First published: 25 December 2001
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 09.02.2021